THE EFFECTIVENESS OF DIGITAL STORYTELLING-BASED HAND PUPPET MEDIA FOR ELEMENTARY SCHOOL STUDENTS - Ana, Marisa; Handayani, Trisni (Jurnal Pendidikan Dasar Flobamorata, 2023)
This study aims to develop digital storytelling-based hand puppet media developed with the ASSURE model, learning Indonesian language material on observing characters in fictional texts in elementary schools, seeing responses, improving skills, and understanding of students. The subjects of this study were fourth grade students of SDN Susukan 06, totaling 23 students in the 2023 school year. Data were collected using tests, questionnaires, interviews, observations, documentation, and field notes. The results of the study are (1) obtained the average score of expert validation with a percentage of 95% with the category "very feasible" (2) the average score of learner responses with a percentage of 93.67% which is included in the "very suitable" category (3) the average posttest score which has increased by 82.17 with the category "very good" so that it can be concluded that digital storytelling-based hand puppet media is feasible to use in the material of looking at characters in fictional texts for grade IV Indonesian language learning and can improve students' skills in telling stories as well as understanding to grade IV students in the material of looking at characters in fictional texts.